MO585EFFECTS OF LANTHANUM CARBONATE AND CALCIUM CARBONATE ON CARDIOVASCULAR CALCIFICATION IN HEMODIALYSIS PATIENTS: A SYSTEMATIC REVIEW AND META-ANALYSIS. (29th May 2021) - Yang, Junlan; Zhang, Xiao liang; Wang, Lina
Abstract: Background and Aims: Commonly used phosphorus-lowering drugs include calcium-containing phosphate-binding agents and non-calcium-containing phosphate-binding agents, the latter mainly including lanthanum carbonate (LC). In recent years, some studies have explored the effect of lanthanum carbonate compared with calcium carbonate on serum calcium. However, the results are different. Therefore, we conducted this review to systematically review and meta-analyze evidence on the efficacy of lanthanum carbonate and calcium carbonate (CC) and the risk of cardiovascular calcification in hemodialysis (HD) patients, and to provide reference for phosphorus-lowering drugs in HD patients. Method: The Cochrane library, PubMed, Web of Science, Chinese journal full-text database (CNKI), WANGFANG DATA and Sino Med were searched between January 1946 and December 2020. The literatures with respect to the randomized controlled clinical trial comparing lanthanum carbonate and calcium carbonate in HD patients were selected. The two evaluators independently collected the data according to the retrieval strategy, screened the literatures according to the inclusion criteria and exclusion criteria, and summarized the literatures that met the criteria. The risk ratio (RR) and 95% confidence interval (CI) were used to represent the counting data. The standard deviation from mean (SMD) and 95%CI were used to represent the continuous variables. Forest plots, sensitivity analysis, Egger regression test and TSA were used to summarized the test performance characteristics. Results: Of 388 original titles screened, data was extracted from 9 studies included 625 participants (Table 1 ). There was moderate-certainty evidence from 9 trials (625 participants) that LC can significantly reduce the progression of coronary artery calcification than CC (SMD= -0.59, 95%CI -0.94 to -0.25, P < 0.01) (Figure 2 ). The serum phosphorus level in the LC group was significantly lower than that in the CC group (SMD= -1.35, 95%CI: -2.33 to -0.36, P < 0.01), and the serum calcium level was significantly reduced (SMD= -1.03, 95% CI: -1.83 to -0.23, P = 0.012). The fibroblast growth factor 23 (FGF-23) level in the LC group was significantly lower than that in the CC group (SMD= -4.80, 95%CI: -7.96 to -1.64, P = 0.003). The Egger regression test of coronary artery calcification score (CACS) showed no potential publication bias ( P = 0.72). Conclusion: In this systematic review, compared with calcium carbonate, lanthanum carbonate can significantly delay the process of coronary artery calcification, and at the same time reduce the patient's serum phosphate, serum calcium and FGF-23. Therefore, we recommend LC as phosphorus-lowering drugs for HD patients.